Analisis Kelayakan Finansial dan Strategi Pengembangan Usaha Comfort Zone Cafe - Terence, Daniel; Karyani, Tuti; Qanti, Sara Ratna; Mukti, Gema Wibawa (Universitas Galuh, 2024)
Comfort Zone Cafe is an MSME located in Bekasi City and was founded in 2021. This cafe has faced challenges over the past year, which was marked by a significant decline in the number of consumers and turnover. One of the main causes of this problem is the absence of a business plan that includes financial feasibility. This research aims to find the right solution to ensure the continuity of Comfort Zone Cafe in the future. The research method used is a qualitative approach with financial ratio analysis, financial feasibility analysis, and SWOT analysis. Financial ratio analysis is used to evaluate business performance, financial feasibility analysis to determine whether Comfort Zone Cafe is worth continuing, and SWOT analysis to formulate the right strategy for the future of this cafe. The research results show that the Comfort Zone Cafe's business performance is still not good, but financially it is still feasible to continue. Therefore, a SWOT analysis was carried out to develop the right strategy to improve the performance and sustainability of the Comfort Zone Cafe business in the future. The results of the financial ratio analysis show that Comfort Zone Cafe is efficient in terms of solvency and activity ratios, but is still not efficient in terms of profitability ratios because sales will decline in 2023 and the costs incurred are very large. The results of the financial feasibility analysis show that Comfort Zone Cafe is worth continuing with an NPV value of IDR 1,978,327, IRR of 8.08%, Net B/C of 1.03, and PP of 1 year 10 months 21 days. The results of the SWOT analysis produced 8 alternative strategies, including developing ideas for attractive branding, maintaining good quality, price and service, using effective promotions, opening cafes earlier, improving financial management, improving product quality, developing more attractive promotions, and improve financial bookkeeping.